Math, asked by priyanshi14007, 3 months ago

Find the value of x^3 - 27y^3 -63xy -343 When x= 3y +7​

Answers

Answered by mathdude500
7

\large\underline{\sf{Solution-}}

Given that

\rm :\longmapsto\:x = 3y + 7

can be rewritten as

\rm :\longmapsto\:x - 3y - 7 = 0

We know that,

\rm :\longmapsto\:If \: a \:  +  \: b \:  +  \: c \:  =  \: 0 \: then \:

\rm :\longmapsto\: \boxed{ \bf{ \:  {a}^{3} +  {b}^{3} +  {c}^{3}  = 3abc}}

So, Here,

\rm :\longmapsto\:a = x

\rm :\longmapsto\:b=  - 3y

\rm :\longmapsto\:c=  - 7

Hence,

\rm :\longmapsto\: {x}^{3} +  {( - 3y)}^{3} +  {( - 7)}^{3} = 3(x)( - 3y)( - 7)

\rm :\longmapsto\: {x}^{3} -  {27y}^{3} - 343 = 63xy

\rm :\longmapsto\: {x}^{3} -  {27y}^{3} - 343  -  63xy = 0

\bf\implies \:\: {x}^{3} -  {27y}^{3}  -  63xy - 343 = 0

Aliter Method :-

Given that,

\rm :\longmapsto\:x = 3y + 7

can be rewritten as

\rm :\longmapsto\:x -  3y  = 7

On cubing both sides, we get

\rm :\longmapsto\: {(x -3 y)}^{3 }  =  {7}^{3}

\rm :\longmapsto\: {x}^{3} -  {(3y)}^{3} - 3(x)(3y)(x - 3y) = 343

\rm :\longmapsto\: {x}^{3} -  {27y}^{3} -9xy(7)= 343

\rm :\longmapsto\: {x}^{3} -  {27y}^{3} -63xy= 343

\rm :\longmapsto\: {x}^{3} -  {27y}^{3} -63xy - 343 = 0

Hence,

\bf\implies \:\: {x}^{3} -  {27y}^{3}  -  63xy - 343 = 0

Additional Information :-

More Identities to know:

(a + b)² = a² + 2ab + b²

(a - b)² = a² - 2ab + b²

a² - b² = (a + b)(a - b)

(a + b)² = (a - b)² + 4ab

(a - b)² = (a + b)² - 4ab

(a + b)² + (a - b)² = 2(a² + b²)

(a + b)³ = a³ + b³ + 3ab(a + b)

(a - b)³ = a³ - b³ - 3ab(a - b)

Similar questions